KOMUNIKASI INTERPERSONAL, SOLUSI ALTERNATIF MENGATASI KEJENUHAN RUTINITAS IBU RUMAH TANGGA - Nihayah, Ulin (Sawwa: Jurnal Studi Gender, 2016)
Saturated feeling often experienced by man as an individual. Attitude saturation on this individual, addressed with a mixed response. Not a few people who stuck with the feeling of saturation that result in actions that might be considered negative because it harms him, one of them housewives. Feeling tired or bored of the routines performed by housewives if not addressed will result in stress that will have an impact on the problem of domestic life. As one alternative that is done to overcome this stress is to do with interpersonal comÂmunication with a partner. Interpersonal communication is intended to help in order to solve problems related to boredom experienced by a housewife.